Isolation and Identification of Endophytic Bacteria from Ficus variegata Blume as Antibacterial Compounds Producer - Shinta Leonita; Maria Bintang; Fachriyan Hasmi Pasaribu (Current Biochemistry, 2015)
Endophytic bacteria can produce antibacterial compounds. Their existence in the medicinal plant of Ficus variegata Blume enables the production of bioactive compounds similar to those contained by the host plants. The purpose of this study was to isolate and identify endophytic bacteria from F. variegata which is potential to produce antibacterial compounds. The methods used include isolation of endophytic bacteria from leaves, stem, aerial root, and fruit of F. variegata plants. Antibacterial activity assay was done against four types of bacteria i.e. Staphylococcus aureus, Bacillus subtillis, Escherichia coli, and Psedomonas aeruginosa. Identification of endophytic bacteria was conducted based on morphological analysis, biochemical test, and molecular analysis of 16S rRNA. Endophytic bacterial culture was extracted by ethyl acetate and analyzed by GC-MS. A total of 29 isolates of endophytic bacteria were obtained from F. variegata. The BH2 isolate was found to have potential activity. Analysis of 16S rRNA showed that BH2 isolate was related to Pseudomonas aeruginosa strain SV1 with 99 % identity. The result of GC-MS analysis showed that the antibacterial compound was Nonanoic acid ethyl ester